Analysis Of Implementation And Obstacles To Sorting 3r-Based Waste At Dr. Iskak Tulungagung Regional Hospital - Ema Mayasari; M. Ali Sodiq; Juvita Herdianty; Daniel Tinoverantus; Adinda Oktavia Rubai; Anna Rashida Nurfaiza; Yustia Rika Amelia; Juniar Ayu Langen Sari (Universitas STRADA Indonesia, 2026)
Waste management is a crucial issue in maintaining environmental quality, including in healthcare facilities that generate large amounts of solid waste. This study aims to analyze the implementation and barriers to 3R (Reduce, Reuse, Recycle)-based waste sorting at Dr. Iskak Tulungagung Regional General Hospital. The study used a qualitative descriptive method, with data collection techniques including in-depth interviews, observation, and documentation. The results indicate that Dr. Iskak Tulungagung Regional General Hospital has implemented the 3R principles by separating domestic and hazardous waste, processing organic waste into liquid and solid fertilizers, and collaborating with third parties through waste banks for inorganic waste management. The implementation of the 3R program is supported by routine coordination activities, annual training, and daily monitoring and evaluation by sanitation and cleaning staff. The main obstacles to the program's implementation are the low awareness of some employees, visitors, and patient attendants regarding waste sorting according to type, as well as limited human resources for the sorting process. Overall, the implementation of the 3R-based waste sorting system at Dr. Iskak Tulungagung Regional General Hospital is considered successful. Dr. Iskak has been operating well and in accordance with national policies, but increased environmental awareness and ongoing support are needed to achieve optimal and environmentally friendly hospital waste management.